Performa Benih Udang Windu yang Diberi Artemia Diperkaya Taurin - Ridwan, R; Baiduri, Moh. Adnan (Journal Galung Tropika, 2021)
This study aimed to analyze the performance of tiger prawn Penaeus monodonseed which were fed taurine-enriched Artemia. The study was conducted by using a completely randomized design.The treatment in this research was taurine enrichment dosage of Artemiathat consist of 4 levels: 0 gL-1 (DPT-0), 0.5 gL-1 (DPT-0.5), 1.0 gL-1 (DPT-1.0) and 1.5 gL-1 (DPT-1.5) in triplicate. Larvae stocked at a density of 50 individu.L-1 were fed Artemianauplii from Mysis-3 to PL-12 stages. Measurement and analysis data to compare the effects of these treatments were tested by analysis of variance (ANOVA) followed by Duncan's multiple range test at a significance level of 0.05. The results showed that the taurine content of Artemia increased significantly and linearly with the enrichment dose of taurine. Furthermore, the specific growth rate and visual quality of larvae increased significantly by feeding taurine-enriched Artemiaof 1.0 gL-1, but increasing the taurine enrichment dose to 1.5 gL-1 in the Artemia was not followed by an increase in these parameters. The vitality and resistance of larvae increased significantly and linearly with increasing in taurine enrichment dose, whereas the survival rate for larvae only increased significantly with 0.5 gL-1 taurine-enriched Artemia. Based on these results, the best post-larval performance of tiger prawns was obtained by feedingArtemia enriched with taurine 1.0–1.5 gL-1.